The Impact of Task-Based Language Teaching on English Speaking Proficiency - Ario Hadiansyah; Jaya Nur Iman; Nike Angraini (CV. ULIL ALBAB CORP, 2025)
This study examines the effectiveness of Task-Based Language Teaching (TBLT) in enhancing students' speaking skills. Using a pre-experimental design, the research involved 25 students in an experimental class engaging in TBLT activities. Pre-test and post-test data revealed significant improvements in their speaking performance, affirming TBLT as an effective method for developing speaking proficiency. Gratitude is extended to my advisor, family, and friends for their invaluable support throughout this research.